Emerging Technologies for Future 5G/ 6G Wireless Communication Networks - Ade Syaheda Wani, Marzuki; Dayang Azra, Awang Mat; Dayang Nurkhairunnisa, Abang Zaidel; Kho, Lee Chin; Hoole, Paul RP (River Publishers, 2020)
This chapter gives an overview of the important and future 5/6G technologies, of which the smart antenna is an integral part. These include, the cloud-based system architecture, cell densification, increasing operating signals to millimeter (mm) electromagnetic waves, massive multi-input-multi-output (MIMO) systems, beam forming, and ubiquitous networks and green communication systems.The 5G system requirements are also presented